Qur’anic Counseling and Psychotherapy: Psychopathological Insights from Surah Yunus Verse 57: Konseling dan Psikoterapi Al-Qur'an: Wawasan Psikopatologis dari Surah Yunus Ayat 57 - Warlan Sukandar; Arif Budiman; Abdul Rashid bin Abdul Aziz (Institut Agama Islam Negeri Kerinci, 2024)
This study aims to develop a Qur’an-based counseling and psychotherapy model, focusing on the analysis of psychopathology found in Surah Yunus, verse 57. The research employs a qualitative approach using thematic exegesis (maudhu‘i) to uncover the deep meaning of the verse and its relevance to modern psychopathology concepts. Data were collected through a literature review involving classical tafsir, contemporary tafsir, and clinical psychology literature, and then analyzed hermeneutically to identify correlations between the Qur’anic message and therapeutic strategies. The findings indicate that Surah Yunus, verse 57 provides a four-dimensional framework for psychological healing: the educative-preventive dimension (al-maw‘izhah), the curative dimension (al-shifā’), the cognitive-preservative dimension (al-hudā), and the affective-spiritual development dimension (al-rahmah). These four dimensions can be adapted into a Qur’anic counseling model that emphasizes a balance between religious knowledge, self-understanding, cognitive restructuring, and spiritual strengthening. The implications of this model offer an alternative integrative approach that combines modern psychological principles with Islamic values for addressing mental disorders, particularly those related to anxiety, depression, and loss of life meaning. This study recommends the implementation of the Qur’anic counseling model based on Surah Yunus, verse 57 in Islamic mental health service settings as a holistic and transformative intervention strategy.